Remdesivir in a pregnant patient with COVID-19 pneumonia. Issue 1 (2nd January 2021) - Dande, Ranadheer; Qureshi, Anum; Persaud, Kia; Puri, Chahat; Zulfiqar, Sajida; Awasthi, Shankar
ABSTRACT: Remdesivir is an antiviral drug currently being studied as a potential treatment of pneumonia caused by infection with SARS-CoV-2. The Adaptive Covid-19 Treatment Trial (ACTT-1) by NIH and the SIMPLE study by Gilead Sciences are two major trials that showed promising results of Remdesivir in the non-pregnant population. We are presenting the case of a pregnant patient who was diagnosed with COVID-19 pneumonia and successfully treated with Remdesivir.